2015
DOI: 10.5120/21687-4792
|View full text |Cite
|
Sign up to set email alerts
|

Improved Haze Removal of Underwater Images using Particle Swarm Optimization

Abstract: The main objective of fog removal algorithm is to estimate the airlight map for the given image and then perform the necessary operations on the image in order to overcome the fog in the image and enhance the quality of the image. The dark channel prior method of fog removal is more suitable and time-saving in real-time systems. In this paper, an efficient approach for fog removal of foggy images based on the combination of dark channel prior and genetic algorithm is presented. It is found that the proposed me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The shrimp video was processed using the deHaze algorithm, which is designed to clarify the object in the video (Figure 1). The dehaze process can increase image visibility and even change the color shift caused by air light [7]. The dehaze process is based on dark channel prior, which derived from the intensity value of color channel is close to zero [8].…”
Section: Datasets Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shrimp video was processed using the deHaze algorithm, which is designed to clarify the object in the video (Figure 1). The dehaze process can increase image visibility and even change the color shift caused by air light [7]. The dehaze process is based on dark channel prior, which derived from the intensity value of color channel is close to zero [8].…”
Section: Datasets Collectionmentioning
confidence: 99%
“…( 5 ) ( 6 ) ( 7 ) Speed is estimated by calculating the distance between each midpoint on the frame passed by the shrimp and comparing it to the number of frames, which can be written as follows.…”
Section: Carapace Length and Swimming Speed Estimationmentioning
confidence: 99%
“…As opposed to various approaches that need the explicit road extraction, this technique offers less constraints through virtue of being applicable with no extra than the homogeneous surface extraction containing a portion of the sky and road within the image. [24] Shriya Sharma (2015) et. al., present algorithm of fog elimination is to airlight map estimate for the provide image and then achieve the required operations on the image in order to overcome the fog in the image and improve image quality.…”
Section: Literature Surveymentioning
confidence: 99%
“…It is found that the proposed method is additional appropriate for obtaining higher image quality than the most of the present method. [25] Rajbeer et. al., present that In the calculating parameter the efficient light intensity also provide the scattering estimates of the atmospheric light, combined Laplace of the air-light is and minimum values provide us the basic light map spread which is further used in the intensity restoration.…”
Section: Literature Surveymentioning
confidence: 99%